(untitled) - Schommers, Wolfram (Singapore, 1998)
This book it is argued that there are obviously no theoretical conceptions of the world which are free of metaphysical elements. This is not only valid in connection with matter but also for the conceptions of space and time. The consequences in connection with modern conceptions of the world are outlined.
Keywords: Matter,Vật lý,Vật chất,Physics; Philosophy,Triết học,Triết học,Philosophy